The Tetrapharmakos (Fourfold Cure) and the Sober Reasoning in Epicurus: A Critical Philosophical Paradigm against the Politicization of Medical Truth? - Markopoulou Αnna Ch. (Journal of Posthumanism, 2022)
In the present paper, we will discuss how the therapeutic effect of Epicurean philosophy as a pharmakon for human passions constitutes a critical philosophical paradigm against the politicization of medical truth. More specifically, we will argue that the concept of correcting habits of thought, which confers a philosophical meaning on the Greek word pharmakon, constructs a dialectical relationship of unity between nature and man. Then we will show that this conception is in contrast to the traditional meaning of pharmakon as an artificial means of therapy, which is ideologicalised in the politicization of medical truth, since it presupposes a technocratic conception leading to a dualism between superior technology, which rules, and inferior human nature, which is ruled. We will argue that establishing an enhancement of human nature as it ensues from the Epicurean ethics of the tetrapharmakos constitutes a critical philosophical paradigm against the politicization of medical truth.